2011
DOI: 10.1111/j.1528-1167.2011.03344.x
|View full text |Cite
|
Sign up to set email alerts
|

The electroencephalogram of idiopathic generalized epilepsy

Abstract: SUMMARYIdiopathic generalized epilepsy (IGE) is classified into several subsyndromes based on clinical and electroencephalography (EEG) features. The EEG signature of IGE is bisynchronous, symmetric, and generalized spikewave complex; although focal, irregular, and so called ''fragments'' of discharges are not uncommon. Other characteristic EEG features include polyspikes, polyspike-wave discharges, occipital intermittent rhythmic delta activity, and photoparoxysmal response. Both human and animal data suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 98 publications
(165 reference statements)
6
76
1
3
Order By: Relevance
“…15,17,18 This study showed abnormal EEG recordings in 6 (35%) out of 17 patients who presented with complex partial seizures and 30 (36%) out of 83 patients who presented with generalized tonic clonic seizures.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 64%
“…15,17,18 This study showed abnormal EEG recordings in 6 (35%) out of 17 patients who presented with complex partial seizures and 30 (36%) out of 83 patients who presented with generalized tonic clonic seizures.…”
Section: Electroencephalography (Eeg)mentioning
confidence: 64%
“…We found EEG signals suggestive of IEDs, or discharges suggesting an intracranial space-occupying mass or brain abnormality (Lacombe et al 2001;Stern 2005;Moeller et al 2011;Seneviratne et al 2012). In a cohort of over 13,000 normal humans, IEDs were found in 0.5% of the cases (Noachtar & R emi 2009) and the chance that healthy persons with IED would develop epilepsy was 2%-3% (Noachtar & R emi 2009;Brigo 2011).…”
Section: Discussionmentioning
confidence: 97%
“…The ambulatory system makes it more convenient to register EEG recordings since horses can walk around in their stable or can be hand-walked. Theoretically, this will increase the likelihood of recording abnormalities (Binnie & Stefan 1999;Moeller et al 2011;Seneviratne et al 2012). Since in humans many pathological events occur during certain phases of sleep (Binnie & Stefan 1999;Overvliet et al 2010), it seems advantageous that the horses showed a surprisingly frequent-occurring sleep pattern during the day, which might be beneficial for capturing abnormal recordings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…between 4 and 12 years (Loiseau et al, 2002), are still classified as generalized (Berg and Plioplys, 2012), although it is questioned whether there are fundamental differences between generalized and focal types of epilepsy (Lüders et al, 2009;Seneviratne et al, 2012;van Luijtelaar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%